PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR TERHADAP KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA - Siti Nurhalimah; Nani Yuliantini; Pebrian Tarmizi (Universitas Bengkulu, 2018)
This research is aimed to know of using surrounding environment as a study resource toward the ability of 5th grade student SDN 74 Kota Bengkulu in writing descriptive text. The research is a quantitative, which use quashy experience method with the matching only pretest-posttest control group design. Population in this research is 5th grade student of SDN 74 Kota Bengkulu. The sample is taken with cluster random sampling technique, VA class is selected as experiment class with 31 students, and VB selected as the control class with 32 students. The reseach instrument is a test to write descriptive text given to students through pretest (before the learning process) and posttest (after the learning process). Research data is analized with descriptive and infrence analysis (t-test). Based on research result t-testt with 5% significance value, it gain tcalculate 2,49 >ttable 2,0. So conclude that there is an influence in using surrounding environment as a study resource toward the ability of 5th grade students SDN 74 Kota Bengkulu in writing descriptive text.